Antecedents and consequences of employee engagement: a conceptual study - Aktar, Alima; Pangil, Faizuniah (Iosrjournals.org, 2017)
Employee engagement is a psychological state of mind of doing the work with full of energy, enthusiasm and dedication which can provide the competitive advantage of an organization. The purpose of this paper is to synthesize prior literature to identify antecedents and consequences of employee engagement. This literature review shows that prior studies examined diverse types of antecedences as well as consequences of employee engagement. Results of these existing studies are varied and inconclusive which leads the importance of further study in order to enhance the clarity of the relationship of employee engagement with its antecedents and consequences.